The Impact of Mixed Emotions on Judgements: A Naturalistic Study During the Fifa World Cup - Berrios-Espinoza, R (Routledge, 2021)
Experiencing mixed emotions, a combination of two oppositely-valenced emotions, has been shown to reduce bias in decision making and improve the accuracy of judgements made. However, most previous research has been limited to laboratory-based experiments. In this pre-registered study, we looked at mixed emotions and judgements in the naturalistic context of watching sport during the FIFA world cup. N = 80 participants reported on mixed emotions before and after each England game during the World Cup, and made score predictions for each game, collecting a total of k = 480 observations. We used a lagged-effect design and multilevel modelling to analyse the data. We found that participants who felt more mixed emotions at the end of a match made significantly more likely score predictions in the following match, indicating that experiencing stronger mixed emotions subsequently predicted more reasonable judgements. This result was supported even after controlling for a number of affective, attitudinal, and socio-demographic variables. This provides evidence that naturally occurring mixed emotions are related to improved real-world judgements. The evidence is discussed through the lens of fantasy realisation theory, and the importance of feeling mixed during decisions involving puzzling or uncertain outcomes is emphasised. © 2020 Informa UK Limited, trading as Taylor & Francis Group.